Politics During and After Covid-19: Science, Health and Social Protest - Bertuzzi, Niccolò; Lagalisse, Erica; Lello, Elisa; Gobo, Giampietro; Sena, Barbara (PARTECIPAZIONE E CONFLITTO, 2023)
Covid-19 represented a total social fact, especially for that part of the world (the so-called Global North and in particular its wealthier component) which is less used to face dramatic crises able to affect fundamental rights and provoke health threats on a daily basis. While acknowledging its enormous impact on individual biographies, political systems and socio-economic equilibria around the planet, however we contrast those interpretations that have tended to naturalize the pandemic event, reading it as unpredictable, unique, disconnected from the dynamics that guide the (mainstream) Western lifestyle and mode of production. On the contrary, the genesis and above all the management of Covid-19 are the result and the mirror of broader dynamics linked to modernity, colonialism, capitalism, in one word of the Capitalocene. For this reason, it is even more correct to speak of a syndemic, to underline the environmental determinants of health, and the social and economic inequalities (re)produced by Covid-19. We therefore consider that interpreting the pandemic/syndemic (and its governance) as a state of exception is at least partial, being instead more useful to identify its unveiling function, able to make some latent or less visible dynamics manifest. Based on such premises, we focus on some nodes of the syndemic governance, highlighting how this contributed to give continuity and accelerate typical dynamics of a neoliberal governance and worldvision. We deal in particular with four key issues: the treatment of "science" by the media; the political history of "public health" and its relationship to the modern state; the construction of legitimate dissent vs. the constructed irrationality of "conspiracy theory"; the outcomes of social protests and in particular their pathologization in the mediatic and public debate. These are also among the main topics which are critically discussed in the thirteen papers that compose this Special Issue, from a variety of disciplinary fields, and with diverse epistemological perspectives and methodological tools.